Application of artificial intelligence techniques in Ms. Pan-Man game : a review - Tan Tse Guan; Jason Teo (Universiti Malaysia Kelantan, 2015)
Artificial Intelligence (AI) techniques are successfully used and applied in a wide range of areas, including manufacturing, engineering, economics, medicine and military. In recent years, there has been an increasing interest in Game Artificial Intelligence or Game AI. Game AI refers to techniques applied in computer and video games such as learning, pathfinding, planning, and many others for creating intelligent and autonomous behaviour to the characters in games. The main objective of this paper is to highlight several most common of the AI techniques for designing and controlling the computer-based characters to play Ms. Pac-Man game between years 2005-2012. The Ms. Pac-Man is one of the games that used as benchmark for comparison of autonomous controllers in a series of international Game AI competitions. An extensive content analysis method was conducted through critical review on previous literature related to the field. Findings highlight, although there was various and unique techniques available, the major limitation of previous studies for creating the Ms. Pac-Man game characters is a lack of generalization capability across different game characters. The findings could provide the future direction for researchers to improve the Generalization A.I capability of game characters in the Game Artificial Intelligence market.